Pengaruh Model Pembelajaran PjBL dengan Pendekatan CTL terhadap Kemampuan Pemecahan Masalah Siswa Kelas V - Isnatul Kurnia; Lilik Bintartik (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2026)
Problem-solving abilities are important for adapting to new situations, and students as the future leaders of civilization, need to have the competence to solve various problems. This has the objective to examine the effect of the PjBL learning model with the CTL approach on the fifth-grade’s problem-solving abilities. This study utilize quantitative approach with a quasi-experimental design and nonequivalent control group design. The subject in this research were fifth-grade at SD Negeri Kalipang 1, with a sample size of 21 students in the control class and 23 students in the experimental class. The experimental class was given treatment of the PjBL learning model with CTL Approach, while the control class was given cooperative learning. The data in this study were collected using observation and tests. This research found that the execution of the CTL-based PjBL Model in the experimental class was 80.6% in the first cycle and 90.42% in the second cycle. From these results, it can be racionated that the implementation of the PjBL learning model with CTL approach was good. Then, the results in the form of pre-tests and post-tests were tested using an independent sample t-test to determine the effect of the treatment given. The results showed a 2-tailed sig. value of 0.001, so it was concluded that H1 was accepted. Thus, it can be concluded that the implementation of the CTL-based PjBL model has a significant effect on the problem-solving abilities of students in fifth-grade.